Pengaruh Kualitas Produk dan Persepsi Harga Terhadap Keputusan Pembelian: Studi pada Konsumen Produk Wardah. - Melani Devita Kusuma Wardani; Alimudin Rizal Rivai (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to test and analyze the effect of product quality and price perceptions on purchasing decisions using quantitative data where the results of this study will be in the form of numbers that have been processed using IBM SPSS 21 software. The population in this study are consumers who know Wardah cosmetic products, and have the desire to buy Wardah cosmetic products. The sampling method in this study uses non-probability sampling with purposive sampling technique where the sample is taken based on certain criteria. The method used in data collection is to use a questionnaire with a Likert measurement scale of 1-7, so that the data obtained is 100 respondents. Data analysis in this study used multiple linear regression. The results showed that product quality had an effect on purchasing decisions and price perceptions had no effect on purchasing decisions.